STUDY OF SEA WAVE ENERGY AND POWER BASED ON TOTAL INDIVIDUAL WAVE HEIGHT AND RMS (ROOT MEAN-SQUARE) WAVE HEIGHT - Fadhil Pratyaksa, Indrawan
The purpose of this research is to calculate wave energy from field observation data and physical model test by analysing the relationship of wave energy formula which is calculated from the total of individual wave energy and energy calculated from root mean-square wave height. Physical model test was done with 1 scenario, with depth of 0.657 m. The data generated from the physical model test was recorded with 0,04 second interval and measured for 30 minutes. Field observation data recorded with 1 second interval and measured for 29 hours then divided by 30 minutes each. Zero-up crossing method was then used to define the wave parameters. To analyze the relationship between wave energy formula, two parameters was made to do the comparison. The two parameters are total individual wave energy and wave energy calculated from root mean-square wave height. The results showed that the wave energy calculated form root mean-square wave height have a slightly different value to the total individual wave energy. The comparison between the wave power is also calculated for physical model test. Wave power comparison showed that wave power calculated form root mean-square wave height have a slightly different value to the total individual wave power.